Elongated magma plumbing system beneath the Coso volcanic field, California, constrained by seismic reflection tomography - Wang, Dongdong (2023)
The magma plumbing in the lower crust beneath the Coso volcanic field (CVF) remains controversial, largely because of the absence of high-resolution lower crustal velocity models. For the first time, we develop a high-resolution crustal P-wave velocity model for the Coso-Ridgecrest region by jointly inverting 137,992 first P and 8,636 PmP travel-time data using an eikonal equation-based seismic reflection tomography method. More than half of the PmP travel times are picked from earthquakes after the 2019 Mw 7.1 Ridgecrest earthquake. Such abundant PmP travel times significantly improve the resolution of the lower crust. Our final velocity model reveals a prominent low-velocity body sitting right beneath the CVF at 5–20 km depths, which we interpret as a rhyolite magma reservoir that supplies heat flux to the hot springs and also feeds the volcanic activities at Coso. We find that the upper-middle crustal low-velocity body dips southwards into the lower crust, extending to regions beneath the Indian Wells Valley and the Garlock Fault at depth greater than 20 km. We ascribe the lower crustal low-velocity body (more than 4% Vp reduction) to a basaltic magma reservoir that connects the melts in the uppermost mantle with the eruptible rhyolitic reservoir at shallower depths. The basaltic magma reservoir constitutes an important part of a continuous N-S elongated crustal magma plumbing system beneath the CVF, formed as a combined result of local extension, faulting, and stress distribution.